Increased ICAM-1 and PECAM-1 Transcription Levels in the Heart of Apo-E Deficient Mice in Comparison to Wild Type (C57BL6). - Zibara, Kazem; Chettab, Kamel; McGregor, Brigitte; Poston, Robin; McGregor, John (Thrombosis and Haemostasis, 2001)
Adhesion molecules and chemoattractants are thought to play a critical role in the homing of leukocytes to sites of vascular lesions. Apo-E deficiency in mice creates an atherosclerotic model that mimics vascular lesions in man. Little is known on the effect of Apo-E deficiency on expression of adhesion molecules in the hearts of these animals. In this study, male C57BL6 and Apo-E deficient mice were fed a chow diet over periods of time (0 to 20 weeks). The transcription levels of major adhesion molecules (ICAM-1, PECAM-1), present in the heart, were followed by northern blots. Immunohistochemistry was used to localize these adhesion molecules in the heart. Results show a significant increase in gene transcription levels of ICAM-1 and PECAM-1 in Apo-E animals, but not wild type, at 16 and 20 weeks of chow diet. Such increase in levels of transcription was not observed in younger Apo-E and C57BL6 animals (0, 6 weeks of diet). ICAM-1 and PECAM-1 were strongly expressed in the endocardium and heart microvessels. In contrast, VCAM-1 was poorly stained, with only an occasional expression on the endocardium and arterioles. Enhanced gene expression levels of heart ICAM-1 and PECAM-1 observed in Apo-E deficient mice, but not in control animals, appears to induce the initial stages of an inflammatory reaction. Such observations, not previously reported, may induce heart vascular remodeling.
Keywords: Atherosclerosis; adhesion molecules; apolipoprotein E; knockout mice; heart; northern